Stanozolol-soaked grafts enhance new bone formation in rat calvarial critical-size defects. (26th July 2017) - Ghiacci, G; Graiani, G; Cacchioli, A; Galli, C; Lumetti, S; Ravanetti, F; Elviri, L; Manfredi, E; Macaluso, G M; Sala, R
Abstract: Androgen hormones play a significant role in regulating bone morphogenesis and in maintaining bone homeostasis throughout life. This study aimed to investigate the local effects of the non-aromatizable androgen stanozolol (ST) on bone regeneration in rats. Bilateral critical-size defects were created in the parietal bone of 26 male Wistar rats: the defect on one side was filled with a deproteinized bovine bone scaffold (DBB) soaked in ST solution (test) and the contralateral with DBB alone (control). Samples were collected at one month and three months. Histomorphometry revealed a significantly higher new bone formation (NB) (24.41% ± 4.14% versus 15.01% ± 2.43%, p < 0.05) and mineral apposition rate (MAR) (9.20 μ m/day ± 0.37 versus 6.50 μ m/day ± 1.09, p < 0.05) in the test versus control group at one month. Accordingly, real time-polymerase chain reaction revealed a consistently higher Runx 2 expression in test samples (fold change test/control: 4.50 ± 1.17, p ≤ 0.05). No morphometrical differences between groups were detected at three months ( p > 0.05). However, test samples were characterized by an increase in blood capillary density from one month (11.43 n mm −2 ± 2.01) to three months (28.26 n mm −2 ± 5.62), providing evidence of a vital remodeling tissue. Control samples presented a decrease of anti-Osterix (SP7)/anti-osteocalcin (BGLAP) (3.9 n mm −2 ± 0.32 versus 1.01 n mm −2 ± 0.20) and alkaline phosphatase (ALP) (12.14 n mm −2 ± 6.29 versus 6.29 n mm −2 ± 2.73) immunohistochemical-positive elements, which was suggestive of a stabilized healing phase. Based on these observations, local ST administration boosted bone regeneration in rat calvarial critical-size defects at one month. This study showed the potential of local steroid delivery in bone regeneration.